Hirschsprung's disease in the UK and Ireland: incidence and anomalies. Issue 8 (9th March 2017) - Bradnock, T J; Knight, M; Kenny, S; Nair, M; Walker, G M
Abstract : Objectives: To describe clinical characteristics and preoperative management of a national cohort of infants with Hirschsprung's disease (HD). Design: Population-based cohort study of all live-born infants with HD born in the UK and Ireland from October 2010 to September 2012. Setting: All 28 paediatric surgical centres in the UK and Ireland. Participants: 305 infants presenting before 6 months of age with histologically proven HD. Main outcome measures: Incidence, clinical characteristics including gestational age, birth weight, gender, associated anomalies; age and clinical features at presentation; and use of rectal washouts or stoma. Results: The incidence of HD in the UK and Ireland was 1.8 per 10 000 live births (95% CI 1.5 to 1.9). Male to female ratio was 3.3:1. An associated anomaly was identified in 23% (69), with 15% (47) having a recognisable syndrome. The proportion of infants who presented and were diagnosed in the neonatal period was 91.5% (279) and 83.9% (256), respectively. 23.9% (73) and 44.2% (135) passed meconium within 24 and 48 hours of birth. 81% (246) first presented to a hospital without tertiary paediatric surgical services, necessitating interhospital transfer. Initial colonic decompression was by rectal washouts in 86.2% (263) and by defunctioning stoma in 12.8% (39). Subsequently, 27.4% (72) of infants failed management with rectal washouts and required a delayed stoma, resulting in 36.4% (111) of infants having a stoma. Conclusions: In this population-based cohort, presentation outside the neonatal period was rare. Nearly half of the infants with HD passed meconium within 48 hours of birth and over one third were managed with a stoma.